Convergence insufficiency in Chinese high school students. (11th September 2018) - Ma, Martin Ming‐Leung; Long, Wen; She, Zhihui; Li, Wanping; Chen, Xuhui; Xie, Lingmei; Scheiman, Mitchell; Liu, Yuling; Chen, Xiang
Abstract : Background: The frequency of convergence insufficiency was determined in a sample of Chinese high school students. The associations between the frequency of convergence insufficiency, gender, refractive error and accommodative insufficiency were investigated. Methods: This was a single‐site, prospective cross‐sectional study. In total, 928 eligible teenagers (mean age 15.9 ± 0.8) from a local high school in Guangzhou, Guangdong Province, China participated in this study. Refraction and binocular vision tests were performed on all eligible participants. The following three signs were used to classify participants: sign 1, exophoria at near at least 4 ▵ greater than at far; sign 2, receded near point of convergence (≥ 6 cm break point); and sign 3, insufficient near positive fusional vergence (that is, failing Sheard's criterion or ≤ 15 ▵ break point). Diagnostic groups of convergence insufficiency classification were defined as follows: (1) 3‐Sign convergence insufficiency (all three signs present); (2) 2‐Sign convergence insufficiency (sign 1 plus sign 2 or 3); (3) 1‐Sign convergence insufficiency (sign 1 only); and (4) no convergence insufficiency (that is, participants not classified into one of the above groups). Results: The number and frequency of individuals with 3‐Sign, 2‐Sign, and 1‐Sign convergence insufficiency as well as no convergence insufficiency group were 25 (2.7 per cent), 119 (12.8 per cent), 303 (32.6 per cent) and 481 (51.8 per cent), respectively. Gender (χ 2  = 36.6, df = 3, p < 0.001), refractive error grouping (χ 2  = 37.7, df = 9, p < 0.001) and accommodative insufficiency (χ 2  = 15.4, df = 3, p = 0.002) were all significantly associated with convergence insufficiency. Male gender, hyperopia, or accommodative insufficiency were more likely to be classified with 3‐Sign convergence insufficiency. The frequency of accommodative insufficiency was 9.5 per cent (88 of 928 participants). Conclusion: Compared to the data from school‐ and clinic‐based populations in the USA and South Africa, the data from this sample of Chinese high school students showed a lower frequency of 3‐Sign convergence insufficiency (2.7 per cent). Convergence insufficiency was associated with refractive error, gender and accommodative insufficiency.